Impact of media on sleep quality of adolescents - Dr. Sunita Koreti; Dr. Gunvant Singh Eske; Dr. Shruti Saxena (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Sleep disturbanceis an important risk factor for the development of depression during adolescence. Excessive electronic media usage at night was a risk factor for adolescents’ sleep disturbance. As late sleep onset can reduce sleep, this sleep/circadian rhythm disturbance may cause brain impairment [1]. We planned to identify sleep quality of school going adolescents as well as predictors on disturbed sleep patterns like Television, Mobile. Methods: A community based cross-sectional analytical study compromising of1000 school going adolescents between 8th to 12th standard studying in government and private schools of city of Gwalior for duration 1 year. Questionnaire prepared on Pittsburg Sleep Quality Index guidelines were distributed to them. Results: In our study the most common cause for sleepdisturbancesamong adolescentswere nightmares(15.4%) followed by sleep latency more than 30 minutes. Prevalence of poor sleep quality (PQSI score>5) was more in 15-17 years age adolescents, class standard 11th and 12th and lower economic status. The mean time of sleeping was 7.1±.67 hours on weekdays and 7.42±0.35 hours on weekends. Increasing usage of mobile internate was found to be singnificantly associated with poor sleep quality in comparison to television watching. Poor sleep has direct corelation with scholastic performance. Conclusion: About one third of the adolescent’s population was having poor quality sleep. Increasing use of mobile internate was found to be singnificantly associated with poor sleep quality Poor sleep has direct corelation with scolastic performance. Sleep assessment must be included in the overall assessment of child’s well-being.